Peran Bhabinkamtibmas Menjaga Stabilitas Keamanan dan Ketertiban Masyarakat Desa Taman Agung Lampung Selatan - Aidil Fitriansyah; Linje Anna Marpaung; Erlina B (Universitas Batanghari Jambi, 2023)
The National Police is responsible for seeking, preventing, and eliminating any symptoms that may appear and may disrupt security and order in the community. The research method is a normative juridical approach and an empirical approach. And concluded with a deductive way of thinking so that it becomes a general description of the answer to the problem based on the results of the study. The results of the research are the Implementation of Perkap Article 1 paragraph (7) Number 1 of 2021 which has been implemented but has not been effective or has been implemented but has not been implemented optimally, this is due to inadequate facilities and infrastructure and residents do not fully understand the importance of maintaining security. and common order. Inhibiting Factors People who do not fully understand the rules and also facilities and infrastructure that are less supportive, and budget constraints. creating Suggestions that all villagers need to support all programs that have been made by bhabinkamtibmas in security and order in the community, increasing socialization and dialogue between residents and members of bhabinkamtibmas in order to create a good partnership relationship.